Test-Retest Reliability of Scotopic and Mesopic Fundus-Controlled Perimetry Using a Modified MAIA (Macular Integrity Assessment) in Normal Eyes - Pfau, Maximilian; Lindner, Moritz; Fleckenstein, Monika; Finger, Robert P.; Rubin, Gary S.; Harmening, Wolf M.; Morales, Marco U.; Holz, Frank G.; Schmitz-Valckenberg, Steffen (Ophthalmologica (Basel), 2017)
Purpose: To assess the intrasession test-retest reliability of scotopic cyan and scotopic red fundus-controlled perimetry (FCP) in normal subjects using a modified MAIA “microperimeter” (macular integrity assessment) device. Methods: Forty-seven normal eyes of 30 subjects (aged 33.8 years) underwent duplicate mesopic (achromatic stimuli, 400-800 nm), scotopic cyan (505 nm), and scotopic red (627 nm) FCP, using a grid of 49 stimuli over 14° of the central retina. Test-retest reliability for pointwise sensitivity (PWS), stability of fixation, reaction time and test duration were analyzed using mixed-effects models. Results: PWS test-retest reliability was good among all 3 types of retinal sensitivity assessments (coefficient of repeatability of 4.75 dB for mesopic, 5.26 dB for scotopic cyan, and 4.06 dB for scotopic red testing). While the mean sensitivity decreased with eccentricity for both mesopic and scotopic red testing, it was highest at 7° eccentricity for the scotopic cyan assessment (p < 0.001). Conclusions: The modified MAIA device allows for reliable scotopic FCP in normal subjects. Our findings suggest that testing of scotopic cyan sensitivity largely reflects rod function.